Pengaruh Motivasi Belajar Terhadap Penyelesaian Tugas Mata Kuliah Hidrolika Mahasiswa Jurusan Pendidikan Teknik Bangunan Fakultas Teknik Universitas Negeri Manado - Tulaka, Titof (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out what is suitable for use in hydraulics courses based on learning motivation for completing assignments for students majoring in Building Engineering Education, Manado State University which can be used as a reference in developing hydraulics learning applications. This research uses a correlational description method. The results of this research show that student motivation for the hydraulics course shows that the influence of student learning motivation on completing course assignments has a positive direction, where from the results of the analysis the regression equation is obtained Ŷ= 14.6442 + 0.3635X, meaning that if there is an increase in changes in learning motivation, then the change in completion of structure course assignments will automatically increase as well. From the results of hypothesis testing, the correlation coefficient r = 0.7697 and determination r2 = 0.5929 are obtained. These results indicate that 59.29% of the variation that occurs in the process of completing hydraulics course assignments is influenced by learning motivation. It should be noted above that the average value of learning motivation is 76% of the expected value, namely 110 (from 22 question items), the average value for completing structured course assignments is 42.27 from the expected value, namely 60 (from 12 question items). B0 value = 14.6442 and B1 value = 0.3635. In this condition, students' completion of hydraulics course assignments only reaches an average score of 42.7, but if students have good learning motivation (optimally) then the level of assignment completion will also increase. This quantitative value can be said to be very good, because the completion of course assignments Students' hydraulics courses are influenced by learning motivation by 59.29% while the rest are influenced by other factors.